Targeting TMEM88 as an Attractive Therapeutic Strategy in Malignant Tumors - Cai, Ming; Ni, Wei-Jian; Wang, Ying-Hong; Wang, Jing-Ji; Zhou, Hong (Frontiers in Oncology, 2022)
According to authoritative surveys, the overall morbidity and mortality of malignant tumors show an upward trend, and it is predicted that this trend will not be well contained in the upcoming new period. Since the influencing factors, pathogenesis, and progression characteristics of malignant tumors have not been fully elucidated, the existing treatment strategies, mainly including surgical resection, ablation therapy and chemotherapy, cannot achieve satisfactory results. Therefore, exploring potential therapeutic targets and clarifying their functions and mechanisms in continuous research and practice will provide new ideas and possibilities for the treatment of malignant tumors. Recently, a double-transmembrane protein named transmembrane protein 88 (TMEM88) was reported to regulate changes in downstream effectors by mediating different signaling pathways and was confirmed to be widely involved in cell proliferation, differentiation, apoptosis and tumor progression. At present, abnormal changes in TMEM88 have been found in breast cancer, ovarian cancer, lung cancer, thyroid cancer and other malignant tumors, which has also attracted the attention of tumor research and attempted to clarify its function and mechanism. However, due to the lack of systematic generalization, comprehensive and detailed research results have not been comprehensively summarized. In view of this, this article will describe in detail the changes in TMEM88 in the occurrence and development of malignant tumors, comprehensively summarize the corresponding molecular mechanisms, and explore the potential of targeting TMEM88 in the treatment of malignant tumors to provide valuable candidate targets and promising intervention strategies for the diagnosis and cure of malignant tumors.